Modelo de gestión para la comercialización de una marca nacional de teléfono celular en el mercado de la ciudad de La Maná año 2015 - Rojas Párraga, Lisseth Katherine (2016)
The current research has the general objective to design a management model for the commercialization of a national brand of cell phone in the market of La Manna 2015, the proposal comes with the purpose of contributing to the commercial sector of La Mana; for which was used exploratory statistical and descriptive research and a was conducted market with study surveys directed at the owners of stores dedicated to the marketing of cellular and prospective customers; The results allowed to determine that the Alcatel brand enjoys greater acceptance, SWOT analysis allowed to detect weaknesses on national mobile brands as a low level of information and advertising; which affects low level of knowledge and preferences of users. Designing strategies like maintain a plan of advertising....